Pneumonia among Children with Congenital Heart Disease: Patterns by Shunt Type in A Tertiary Hospital in Indonesia - Aris Bayu Retnaningsih Alisyah Maria; Putri Amelia; Fathia Meirina; Juliandi Harahap; Lily Irsa; Olga Rasiyanti Siregar (Indonesian Journal of Global Health Research, 2026)
Congenital Heart Disease (CHD) in children is frequently associated with lower respiratory tract infections, particularly pneumonia. Pneumonia risk in CHD is influenced by shunt type, defect size, nutritional status, yet local data regarding these associations remains limited. To determine the incidence of pneumonia in children with CHD and to analyze its association with shunt type and defect size. This retrospective cross-sectional study consecutively extracted demographic and clinical data—including CHD shunt type and defect size, nutritional status, and pneumonia diagnosis—from 134 echocardiography-confirmed medical records of hospitalized and outpatient pediatric CHD treated at Adam Malik General Hospital, Medan, from January 2022 to December 2024. Data associations were analyzed using Chi-square or Fisher’s exact tests, and prevalence ratios (PR) were calculated. Pneumonia occurred in 32.8% (44/134) of children with CHD. A higher proportion of pneumonia was observed in acyanotic CHD compared with cyanotic CHD (40.3% vs. 25.4%; PR 1.57; p = 0.066). Among acyanotic CHD, pneumonia was more frequent in children with large defects than in those with moderate to small defects (47.0% vs. 38.0%; PR 1.24; p = 0.511). Pneumonia is a frequent complication in children with CHD. Acyanotic CHD and larger defect size show a tendency toward increased pneumonia risk, although no statistically significant associations were identified.